Development in therapeutic strategies for allergic conjunctivitis - Singh, Neha; Mazumder, Rupa; Monika, Monika; Sakshi, Sakshi; Khan, Fahad; Kumar, Bimlesh (Trends in Immunotherapy, 2023)
Conjunctivitis, also known as pink eye, is a conjunctival inflammation. It is brought on by bacteria, viruses, toxins, and allergies, including coronaviruses, the most frequent reason being allergic conjunctivitis (AC), which is brought on by exposure to pollutants like pollen, animal hair, or mold. The primary contributor to it is the linkage of immunoglobulin E caused by allergens and receptors on stimulated conjunctival mast cells. As a consequence, mast cells are degranulated, along with the release of histamine, cytokines, chemokines, and lipid mediators. The particular eye tissues impacted and the immune mechanism(s) (both local and systemic) that are involved all play a role in the clinical course, length, intensity, and co-morbidities. It frequently occurs in conjunction with allergic rhinitis, also known as allergic rhino-conjunctivitis and other allergy conditions. Atopic keratoconjunctivitis, giant papillary conjunctivitis, seasonal and perennial conjunctivitis, and vernal keratoconjunctivitis are the different types of allergic conjunctivitis. Ocular allergies are frequently misdiagnosed and undertreated, despite the emergence of innovative therapeutic strategies. This review focuses on several previously published studies to discuss the available therapeutic options for treating allergic conjunctivitis as well as the potential targets for the therapies. The association of conjunctivitis with COVID-19, along with recent patents and research, has also been explored.